'Tools of the Employers' Federation': The Derry Lockout of 1924. Issue 1 (1st April 2022) - Dineen, Luke
Abstract : This article chronicles the industrial crisis that took place in Derry in the summer of 1924, when the city was engulfed by mass strikes and a lockout in its staple industry, shirt making. The article begins by putting Derry in its socio-economic and political context, illustrating how sectarian and gender divisions determined the local employment structure. It demonstrates how the Irish revolution, the partition of Ireland, labour militancy and unionist gerrymandering of Derry Corporation laid the foundations for the intense episode of class conflict that took place in the city in the summer of 1924. It describes how the crisis emerged and how, for a six-week period, it made Derry the most strike-ridden city for its size and population in either Britain or Ireland, with tragic social consequences for its inhabitants. There is a strong emphasis on detailing the strike of the corporation employees because their wage demand became embroiled in the political conflict between nationalists and unionists for control of the city. The article concludes by analysing the lockout's immediate outcome and long-term ramifications and scrutinizes what role sectarianism played in the labour movement in Northern Ireland before, during, and after the crisis.